Penyuluhan Hukum Perdata Terkait Prosedur Pengurusan Hak Milik Tanah bagi Warga Kelurahan Lalang Medan Sunggal - Nasution, Hari Gunawan; Mina, Mina; Juniarti, Putri; Lubis, Junaidi (Universitas Pahlawan Tuanku Tambusai, 2026)
The issue of land ownership disputes and the lack of awareness among residents about land rights certification has become an interesting discussion in the Lalang area, Medan Sunggal. Most people only rely on a certificate of hereditary physical possession, without a Certificate of Ownership. This legal counseling activity is designed to educate the Lalang community about the procedures for applying for their land titles. The approach used is active socialization, question and answer sessions on land conflicts. The content of counseling is centered on the regulations in Law Number 5 of 1960 concerning Basic Agrarian Regulations. The output of this activity showed a real increase in public understanding of the flow of land administration, with an average increase in understanding of 80% based on assessments before and after the session. The community began to understand the difference in proof of ownership such as girik, the sub-district head certificate and SHM as the highest ownership recognition document. In conclusion, this activity succeeded in fostering public awareness to immediately replace their proof of ownership in anticipation of potential legal disputes in the future.